DIFFERENCES IN SOME PERSONALITY TRAITS BETWEEN VOLLEYBALL AND FOOTBALL PLAYERS - Savić, Zoran; Karaleić, Slađan; Nešić, Goran (Scientific Journal Management in Sports, 2014)
Scientific approach is used to study a man’s personality, abilities and other characteristics, their interrelations, as well as the structure of numerous factors of the anthropological status necessary for success in sport. It is very important that children, during their first years in sports, are directed to practice those sports which match their psychosomatic status and in which they will achieve the best results. It is impossible in kinesiology and anthropology to measure those factors which are necessary for success in sports directly, but we deduce from Weg indicators, i.e. reactions, about them. It implies that science (kinesiology, anthropology, and others) is responsible for discovering methods which enable determination of factors which are essential for success in sport. This research should help solving some of these prob- lems, and it should objectively determine conative status of volleyball and football players on the same level of competition as well as provide a contribution to improvement of these sports.